Responsible use of water and waste production of waste in homes during the pandemic (COVID-19): a pedagogical experience in a school located in a rural zone in the Amazon (Research, Society and Development, 2022)
Introduction:  This work brings reflections about the use of water, energy, and waste production of a group of students from a public school in a school located in a rural area of Rondônia and aimed at thinking about environmental questions without ignoring the dynamics of the current scenario. Methods: The first step relied on remote meetings with the students of the previously mentioned schools. Further, educational materials were elaborated. The activities were applied using the following tools: Whatsapp for individual talks and orientations; Google Meet: for group discussions. The themes addressed in the classes were: “Water; conscient use of energy and production of waste”. Results and Discussion: The analysis enabled us to observe important consequences generated by the pandemic. Of 45 students, 21 reported to have consumed up to 5 liters of water/minute during baths. With respect to electric energy, 40 students related the decrease in energy consumption with financial saving. With respect to waste production, 80% reported to have burnt the waste and 27% reported that the organic waste is used for animal feed and as fertilizers for plants. Many students were surprised to know the how much water they spend in their homes. With respect to energy consumption decrease, the students had difficulty in saving energy. Regarding waste disposal, the majority reported doing it the wrong way. Conclusion: The activities developed proved to be relevant for students' understanding of water, electricity and waste generation.